The effect of fretting conditions on the lifetime of aero-engine dry film lubricants systems - Laolu-Balogun, Emmanuel (2023)
This study was initiated to address existing fretting failure modes of the aero engine fan blade root components which are protected through the application of a bonded MoS2-based dry film lubricant (DFL), with a focus upon understanding the wear of the DFL system as a route to its lifetime extension. Fretting wear tests have been conducted over a wide range of testing conditions on Ti-6Al-4V specimens which are coated with a DFL system to understand the driving wear and damage mechanisms and reveal pathways to which the extension of fretting lifetimes could be achieved.